Differential Effects of Hip Rotation Range on Knee Abduction Biomechanics during Double-Legged Landing between Males and Females - Tadashi Yasuda; Keiichi Oyanagi; Miyu Nakagaki; Hiromitsu Itoh (Asian Society of Kinesiology, 2020)
Objectives Dynamic knee valgus is composed of hip-knee coupling. While females differ from males in passive hip motion, hip rotation range may alter muscle mechanics and neuromuscular activity. This study aimed to compare knee abduction biomechanics during double-legged drop-landing between males and females with different hip rotation ranges. Methods This study included five females with the range of hip internal rotation (IR) > the range of hip external rotation (ER), five females with ER>IR, four males with IR>ER, and five males with ER>IR. There was no difference in other hip motions among them or no difference in hip muscle strength between the same sex groups. Three-dimensional motion analyses of the hip and knee joints were performed during double-legged drop-landing. Results Multiple regression analysis of females with IR>ER showed that peak knee abduction moment (KAM) was associated with maximal hip abduction moment before detecting peak KAM whereas peak knee abduction angle (KAA) correlated with no variable. In females with ER>IR, peak KAM was associated with maximal hip ER moment before detecting peak KAM, hip ER muscle strength and hip adduction range while peak KAA correlated with peak hip abduction moment before detecting peak KAM. In males with IR>ER, peak KAM was associated with hip ER range and hip adductor strength whereas peak KAA correlated with maximal hip ER moment and maximal hip IR angle during landing. In males with ER>IR, peak KAM was associated with hip extensor strength, hip abduction range and hip flexion range whereas peak KAA correlated with hip ER moment before detecting peak KAM, hip ER muscle strength, and hip adduction range. Conclusions Hip rotation range may differentially affect hip-knee coupling strategy for knee abduction control during double-legged drop-landing between males and females.